Adopting a model of antimicrobial stewardship program to anti-tubercular treatment stewardship: A single-centre experience from a private tertiary care hospital in South India. - Swathy S Samban; Akhilesh Kunoor; Preetha Prasanna; Malavika Krishnakumar; Nandita Shashindran; Chithira V Nair; Abhinandh Babu; Ananth Ram K J; Sivapriya G Nair; Subhash Chandra; Kiran G Kulirankal; Georg Gutjahr; et al. (PLoS ONE)
Tuberculosis (TB) remains a significant public health challenge in Low- and Middle-Income Countries (LMIC). Inappropriate use of Anti-Tubercular Treatment (ATT) undermines treatment efficacy and could contribute to drug resistance. While antimicrobial stewardship programs (AMSP) are well established, anti-tubercular treatment stewardship programs (ATTSP) in private hospitals do not have an established model. An AMSP model in a private tertiary care hospital in South India was repurposed to monitor the prescription appropriateness of ATT. A multidisciplinary team evaluated the ATT prescription appropriateness among inpatients over a one-year period with the 4R's criteria: Right Indication, Right Drug, Right Dose, and Right Frequency. The ATTSP team filed recommendations for inappropriate prescriptions to the primary clinical care team, and compliance to the recommendations was documented within 48 hours. During the study period, 172 ATT prescriptions were evaluated. Inappropriate dose and drug prescriptions were found in 16% and 7%, respectively. The primary clinical care teams complied with 83% of the recommendations within 48 hours. The potential impact of implementing the ATTSP model nationwide was assessed using published data, suggesting that the opportunities to correct inappropriate prescriptions could reach a quarter million. The study provides a proof of concept that an ATTSP can be successfully implemented in a TB endemic, resource-constrained setting. Extrapolation for implementing ATTSP across the country has the potential for huge public health benefits.